Effect of mycorrhizal inoculation and phosphorus levels on growth and yield of wheat and maize crops grown on a phosphorus deficient sandy soil - Pharudi, Joseph Albert (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScAgric (Agronomy))--University of Stellenbosch, 2010.